ANALISIS PENGARUH SOFTSKILL, PENGHARGAAN FINANSIAL, DAN PERTIMBANGAN PASAR KERJA TERHADAP KARIR AKUNTAN PUBLIK - Chrisna Eliano Mangeka; Ika Kristianti (Riset Manajemen dan Akuntansi, 2021)
Analysis of Soft Skill Influence, Financial Reward, and Labor Market Considerations on intention of A Public Accountant Career. This study aims to know the relationship between soft skill, financial reward, and Labor Market Considerations on intention of a public accountant career. The sample collection of this study has been done by the university students of Faculty of Economy and Business of UKSW batch 2017 and 2018. Data processing is conducted by using quantitative approach with Linear Regression Analysis. The amount of sample is about 186 respondents, 90 respondents from batch 2017 and 96 respondents from batch 2018. The data was obtained by spreading questionnaire on google form. The results of this study identify that soft skill, financial reward, and labor market considerations have significant effects to public accountant career